Exploring academic freedom, institutional autonomy, and public accountability in the global landscape of private higher education - Moodley, M. (South African Journal of Higher Education, 2025)
In the dynamic landscape of South African higher education governance, this paper explores the intricate relationship between “academic freedom”, “institutional autonomy”, and “public accountability”. Over decades, the Council on Higher Education (CHE) has undertaken a comprehensive exploration of these foundational principles, initiating a national dialogue through research initiatives and publications. However, recent developments such as the Covid-19 pandemic underscore the imperative to delve deeper into this discourse, as globalisation is quickly becoming a critical external influence on higher education. Focusing on the subtheme: governance of education in a globalised arena, within the matrix of “academic freedom”, “institutional autonomy”, and “public accountability”, the article critically examines the interplay between these essential triadic elements and the overarching impact of higher education governance. Therefore, the aim is to elucidate how these principles intersect and shape the landscape of governance as private higher education institutions become more globalised. Methodologically, a Scoping Review was conducted to offer a wide-ranging outline of the existing body of knowledge. This involved systematically searching, selecting, and synthesising relevant academic literature, journal articles, and websites. Drawing on recent scholarly works, the article navigates the compliance landscape, emphasizing the delicate balance between regulation and “institutional autonomy” within a more globalized educational framework. As the global sphere increasingly influences higher education, the study navigates the compliance landscape, emphasising the subtle balance between regulation and “institutional autonomy” within a more globalized educational framework. Building on the CHE's groundwork over the years in South Africa (S.A.), this study provides insights and “pathways” towards a more global, adaptive, and responsive governance framework for private higher education institutions.